The 43rd Annual IEEE Symposium on Foundations of Computer Science, 2002. Proceedings.
DOI: 10.1109/sfcs.2002.1181977
|View full text |Cite
|
Sign up to set email alerts
|

On the decidability of self-assembly of infinite ribbons

Abstract: Self-assembly, the process by which objects autonomously come together to form complex structures, is omnipresent in the physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…Tile assemblies are extensively studied mathematical objects [1], [6], [37], [41], [44]. Our own prior work has developed the notion of efficient computation with tile assemblies and constructed efficient assemblies to add and multiply integers [8], factor integers [9], and solve NP-complete problems [10], [11], [12].…”
Section: Computing With Tilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tile assemblies are extensively studied mathematical objects [1], [6], [37], [41], [44]. Our own prior work has developed the notion of efficient computation with tile assemblies and constructed efficient assemblies to add and multiply integers [8], factor integers [9], and solve NP-complete problems [10], [11], [12].…”
Section: Computing With Tilesmentioning
confidence: 99%
“…Similarly, the recruitment procedure requires five operations, as described in Section 3.2.3, each also concluded by sending a single network packet; let the time for these operations be denoted as 5u. Thus, the time required by each node is summarized by (1). This analysis is specific to 3-SAT, but the running times for other NPcomplete problems will be very similar, since the fastest growing factor of 2 n will be the same.…”
Section: Efficiencymentioning
confidence: 99%
“…Adleman et al (Adleman et al 2002b) showed that the tile assembly model with s = 1 is Turing-universal.…”
Section: Tile Assembly Model Definitionsmentioning
confidence: 99%
“…Specifically, self-assembly is the process of simple objects coming together and combining to form complex structures. Computer scientists and nanotechnologiests are interested in studying self-assembly because it is capable of computing functions (Adleman 2000; Adleman et al 2002b;Berger 1966;Winfree 1998b), assembling complex shapes (Adleman et al 2002a;Rothemund and Winfree 2000;Soloveichik and Winfree 2007), and guiding distributed robotics systems (Abelson et al 2000;Brun and Reishus 2009;McLurkin et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Tiles can stick together under certain conditions when their abutting sides' labels match. The tile assembly model has been shown to be Turing universal [2,23]. The tile assembly model is a computational model that is somewhat similar to cellular automata, but instead of being able to switch state, the individual square "automata" (called "tiles" precisely because they cannot change state) attach to other tiles following simple matching rules.…”
Section: Tile Architectural Stylementioning
confidence: 99%